2017
DOI: 10.1111/hex.12529
|View full text |Cite
|
Sign up to set email alerts
|

Communication challenges experienced by migrants with cancer: A comparison of migrant and English‐speaking Australian‐born cancer patients

Abstract: ObjectivesUnderstanding the difficulties faced by different migrant groups is vital to address disparities and inform targeted health‐care service delivery. Migrant oncology patients experience increased morbidity, mortality and psychological distress, with this tentatively linked to language and communication difficulties. The objective of this exploratory study was to investigate the communication barriers and challenges experienced by Arabic, Greek and Chinese (Mandarin and Cantonese) speaking oncology pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 40 publications
2
47
1
Order By: Relevance
“…Regarding communication challenges, an Australian comparison study revealed that Chinese migrant cancer patients experienced more difficulties with understanding the healthcare system and communicating with their health care team, compared with their Arabic and Greek migrant counterparts . Although using interpreters could potentially eliminate communication barriers, the quality of such services is questionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding communication challenges, an Australian comparison study revealed that Chinese migrant cancer patients experienced more difficulties with understanding the healthcare system and communicating with their health care team, compared with their Arabic and Greek migrant counterparts . Although using interpreters could potentially eliminate communication barriers, the quality of such services is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Interpreters are also not always accessible when required or available in the range of language groups . Despite the significant communication challenges, Chinese migrants in Australia and the United States have also shared positive experiences where they felt comfortable with the interpreter and spoke favorably about their interaction with their doctor …”
Section: Introductionmentioning
confidence: 99%
“…Not all migrant groups experience the same level of communication difficulties . Nor do all patients want communication interventions; in some cases, these tools directly contradict cultural norms such as not questioning doctors, or utilising assistance only from interpreters or family .…”
Section: Discussionmentioning
confidence: 99%
“…Time pressures in consultations have resulted in suboptimal provision of information to migrants, regardless of interpreter presence, and significant numbers of migrant patients have incorrect understanding regarding their cancer diagnosis . Further, limitations in literacy and health literacy, including understanding of a foreign healthcare system, can further compound difficulties with understanding and remembering health information . While research data cited is country‐specific, communication barriers and lack of understanding regarding novel healthcare systems can be potentially universal for migrants within new host countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation